2009
DOI: 10.2105/ajph.2009.165423
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Household Environmental Intervention Delivered by Lay Health Workers on Asthma Symptom Control in Urban, Disadvantaged Children With Asthma

Abstract: Objectives. We examined whether a home-based educational and environmental intervention delivered by lay health educators would improve asthma symptom control in inner-city children with asthma. Methods. Children 2 to 16 years of age with diagnosed asthma and at least 1 asthma-related hospitalization or 2 emergency visits in the prior year were randomly assigned into 2 groups (immediate and delayed intervention) in a crossover study. Each group participated in the active phase (intervention) and the inactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 12 publications
(15 reference statements)
3
97
1
Order By: Relevance
“…48 There were three cohort studies that examined ED use, two of which showed significant decreases in ED use in the intervention group. 49,50 Hospitalizations Seventeen studies (50%) assessed the effect of the CHW intervention on hospitalizations, primarily during the CHW intervention. Of the seven RCTs, six showed no significant decrease in hospitalizations relative to a control or a randomized observation group.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
See 2 more Smart Citations
“…48 There were three cohort studies that examined ED use, two of which showed significant decreases in ED use in the intervention group. 49,50 Hospitalizations Seventeen studies (50%) assessed the effect of the CHW intervention on hospitalizations, primarily during the CHW intervention. Of the seven RCTs, six showed no significant decrease in hospitalizations relative to a control or a randomized observation group.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
“…One showed a decrease in costs without significance given 52 ; two indicated a significant decrease relative to an observation cohort. 5,49 Urgent Care Visits…”
Section: Emergency Department Visitsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11,12 Cracks allow pests such as rodents and bugs to enter the home. 12 Inadequate ventilation can result in high concentrations of environmental tobacco smoke, allergens, carbon dioxide, radon, and volatile organic compounds. 12 The effects of these household airborne exposures on asthma are very complex.…”
mentioning
confidence: 99%
“…12 Inadequate ventilation can result in high concentrations of environmental tobacco smoke, allergens, carbon dioxide, radon, and volatile organic compounds. 12 The effects of these household airborne exposures on asthma are very complex. They can be further modified by many coexposures such as endotoxin and nitrogen oxides further complicating the relationships between indoor environmental parameters and asthma-related outcomes.…”
mentioning
confidence: 99%